De-escalation of axillary surgery in early breast cancer: translating ACOSOG Z0011 study into clinical practice for breast-conserving surgery patients with positive sentinel lymph node biopsy - Mehmet Furkan Sağdıç; Burak Dinçer; Cihangir Özaslan (BMC Cancer)
Abstract Purpose This retrospective study aimed to compare patients eligible for the Z0011 study with and without axillary lymph node dissection (ALND) by overall survival (OS), disease-free survival (DFS), and loco-regional recurrence. Methods We carried out this study with the data from early-stage breast cancer patients (T1, T2, and clinical node-negative) undergoing breast-conserving surgery (BCS) and receiving adjuvant systemic therapy (chemotherapy or endocrine therapy) and adjuvant radiotherapy after sentinel lymph node biopsy (SLNB) at Ankara Oncology Hospital between January 2018–2024. We screened the data from a total of 1,218 patients and selected 126 patients with ALND and 67 patients without ALND. All selected patients satisfied the Z0011 criteria. We excluded mastectomy and metastatic patients, those without SLNB, patients with more than two positive lymph nodes, and those receiving neoadjuvant chemotherapy. Then, we compared groups by OS, DFS, and locoregional recurrence. Results While the 5-year overall survival was 98.5% (95% CI, 95.8–100.0%) in the Z0011 group, it was 95.2% (95% CI, 92.1–98.3%) in the Z0011-eligible group. The 5-year DFS rate was 97.0% (95% CI, 92.0–99.0%) and 94.4% (95% CI, 91.2–97.0%) in the groups, respectively. We did not discover recurrence in the axial lymph nodes and breast at a mean follow-up of 69 months (67.46–70.43). Conclusion In summary, the present study demonstrated that the omission of ALND does not exert any significant influence on OS, DFS, and locoregional recurrence among patients satisfying the ACOSOG Z0011 criteria.